COMPARATIVE ESTIMATE OF SOME TUMOR MARKERS IN FEMALES WITH COLON CANCER: A CLINICAL STUDY IN MOSUL CITY - Mostafa, Shaimaa Obaid; Al-Hayali , Haitham L; Hasan, Mowafak K (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study seeks to identify tumor parameters that help detect the different stages of malignant tumors. Method: Blood samples were gathered from 43 females undergoing colonoscopies in hospitals across Mosul, and 18 individuals who were healthy. After colectomy for cancer, the malignant tumor samples were divided into three groups depending on the tumor stages and tested using the ELISA method, with comparison control groups. Results: The ratios such as L/M and P/L showed meaningful differences between stages, which provides differences in the immune system response of patients. In early-stage cancer, markers like Septin-9, HIF-1α, and cf-DNA showed significant differences by tumor stage in women in identifying colon cancer progression. Novelty: The diagnosis and development of colon cancer can be understood with the help of VCAM-1, Septin-9, HIF-1α, and cf-DNA.